Functioning of Representations and Warranties in Project Finance - Cornejo Gemer, Nicolás (2025)
This article first describes the main characteristics of Project Finance, the legal relationships that are built around a financing operation of this type and the common structure of loan agreements. Then, a specific part of the structure of loan agreements, namely the clause containing the representations and warranties, is discussed in more detail. The purpose, content, negotiation of representations and warranties and finally the consequences of their breach are explained.